Pengaruh Beban Kerjacoder Dan Kelengkapan Informasi Penunjang Terhadap Keakuratan Code Rawat Inap Bpjs Di Rspau Dr.S Hardjolukito Yogyakarta - Murtiningtyas, Galih; , Ibnu Mardiyoko, SKM., MM; , Sri Sugiarsi, SKM, M.Kes (2015)
A limited number of officers coder with a high workload lead coder work less effective. Completeness Supporting Information is one of the important things for officers coder to determine the primary code and a secondary code. The purpose of this study was to determine the effect of workload coder and completeness of the information supporting the accuracy of code on a medical record file BPJS patient hospitalization. This type of research is observational. The study design approach time series (data series of the time). while the analysis of data using multiple linear regression. Object of this research is the Medical Record file. The collection of data by observation. Results of this study indicate In Partial there is significant influence between the workload for the accuracy of the code on the value of p = 0.001, partial no pengarauh significantly between the completeness of supporting information to keakuratn code with p = 0.466, no effect simultaneously between workload and completeness of the information supporting the accuracy of the code on the value of p = 0.001.